Factors Influencing Cost Overruns in Government Construction Projects in Southwest Papua (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2026)
Cost overruns remain one of the most persistent issues affecting the successful delivery of government construction projects, particularly in geographically challenging regions such as Southwest Papua, Indonesia. Limited accessibility, complex logistics, fluctuating material prices, and project uncertainties frequently increase construction costs beyond the planned budget. This study investigates how social factors, geographical conditions, and project risk contribute to cost overruns in government construction projects. Data were collected through a questionnaire survey involving 233 respondents representing contractors, consultants, and government agencies engaged in public infrastructure projects. The proposed conceptual model was analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings demonstrate that all three independent variables significantly influence project cost overruns, with geographical factors showing the strongest positive effect among the examined determinants. The structural model also exhibits satisfactory predictive capability, indicating that the proposed framework adequately explains cost overrun behaviour in the study area. These findings provide practical insights for government agencies and construction practitioners in improving project planning, strengthening risk management, and developing more realistic cost estimation strategies for infrastructure projects located in remote regions.